2021
DOI: 10.1021/acscatal.1c00134
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic Evolution of a Peroxidase-like Artificial Metalloenzyme

Abstract: Directed evolution has helped enzyme engineering to remarkable successes in the past. A main challenge in directed evolution is to find the most suitable starting point, that is, an enzyme that allows maximum "evolvability". Consisting of a synthetic cofactor embedded in a protein scaffold, artificial metalloenzymes (ArMs) are reminiscent of rough-hewn ancestral metalloproteins and thus could provide an evolutionarily clean slate. Here, we report the design and directed evolution of an ArM with peroxidase-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…Although the high-throughput screening techniques have significantly improved the size of directed-evolution libraries that can be screened, a big problem remains the prediction of and navigation along evolutionary trajectories. On the one hand, due to its mutagenetic constraint to cover only narrow patches of sequence space, the variants generated and cataloged in the library highly depend on the choice of the starting sequences . On the other hand, the progression from each generation of the library to the next relies on an understanding of how to properly combine improved substitutions .…”
Section: Enzyme Engineering Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the high-throughput screening techniques have significantly improved the size of directed-evolution libraries that can be screened, a big problem remains the prediction of and navigation along evolutionary trajectories. On the one hand, due to its mutagenetic constraint to cover only narrow patches of sequence space, the variants generated and cataloged in the library highly depend on the choice of the starting sequences . On the other hand, the progression from each generation of the library to the next relies on an understanding of how to properly combine improved substitutions .…”
Section: Enzyme Engineering Strategiesmentioning
confidence: 99%
“…On the one hand, due to its mutagenetic constraint to cover only narrow patches of sequence space, the variants generated and cataloged in the library highly depend on the choice of the starting sequences. 48 On the other hand, the progression from each generation of the library to the next relies on an understanding of how to properly combine improved substitutions. 4 State-of-the-art experimental approaches often compensate for this problem by relying on libraries with high sequence diversity or sequence saturation approaches.…”
Section: Directed Evolutionmentioning
confidence: 99%
“…Protein engineering emerges as a powerful tool to optimize enzymes to achieve the desired properties. Charge engineering/modification on enzymes has been shown to be a promising approach to tailoring the enzyme resistance in ILs. , In this regard, Nordwald et al fine-tuned the positive-to-negative charged amino acid ratio of chymotrypsin (from bovine pancreas) and observed an increased half-life (1.6- and 4.3-fold) relative to wild-type chymotrypsin in 1-butyl-3-methylimidazolium chloride ([BMIM]­Cl, 20 wt %) and 1-ethyl-3-methylimidazolium ethylsulfate ([EMIM]­[EtSO 4 ], 20 wt %), respectively . Moreover, half-lives of Candida rugosa lipase and Carica papaya papain in [BMIM]Cl were also enhanced by applying the similarly charged amino acid ratio strategy …”
Section: Introductionmentioning
confidence: 99%
“…Although these studies have made significant progress in the mechanistic understanding of protein–protectant systems, the inconsequential statements and reasoning indicated that further studies were still required. Also, more and more studies proved the importance of quantitative experimental evidence to compare with theoretical and molecular dynamics (MD) simulation results. …”
Section: Introductionmentioning
confidence: 99%